2021
DOI: 10.1093/heapro/daab052
|View full text |Cite
|
Sign up to set email alerts
|

The health and well-being impacts of a work integration social enterprise from a systems perspective

Abstract: Summary Recent research has drawn upon the social determinants of health (SDH) framework to attempt to systematize the relationship between social enterprise and health. In this article, we adopt a realist evaluation approach to conceptualize social enterprises, and work integration social enterprises in particular, as ‘complex interventions’ that necessarily produce differential health outcomes for their beneficiaries, communities and staff. Drawing upon the findings from four social enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Specifically, involvement in social enterprise improved people's mental health, self-reliance/esteem and health behaviours, reduced stigmatization and built social capital. Scholars are starting to explore the organisational features of social enterprise that enable them to achieve these health and wellbeing outcomes [10,29,30].…”
Section: Organisational Structures and Health And Well-being Of Emplo...mentioning
confidence: 99%
“…Specifically, involvement in social enterprise improved people's mental health, self-reliance/esteem and health behaviours, reduced stigmatization and built social capital. Scholars are starting to explore the organisational features of social enterprise that enable them to achieve these health and wellbeing outcomes [10,29,30].…”
Section: Organisational Structures and Health And Well-being Of Emplo...mentioning
confidence: 99%
“…It is worth mentioning that they also pointed out that they learned their new work without much pressure and stress and that they were able to socialize and establish a social network with co-workers. Similarly, Joyce et al [28] found that employees they interviewed felt a strong sense of connection to other people employed in the organization. In a study carried out in Manchester, UK, employees working in an SE perceived that they had adequate control over their jobs, as well as flexibility and support, and that they were involved in decision making and had received appropriate training and development, all of which contributed to job satisfaction [52].…”
Section: Discussionmentioning
confidence: 89%
“…In relation to Work Integration Social Enterprises (WISEs), which are the target of this study, evidence shows that there is an association between their activities and improved wellbeing among users [23,28]. For instance, Barraket et al recently reported that, in Australia, WISEs can increase young people's access to employment and/or employability, improve their self-reported mental health and wellbeing, and positively influence healthier behaviours, including healthy eating, reduced smoking, and reduced drug use [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that there was no discussion of ‘best practice’ in evaluation of this field evident in the literature, these findings represent the first assessment of evaluative research related to SE and ID. It is possible that lessons could be learned from the broader SE field, particularly WISE related to other populations (e.g., Barraket, 2014; Hazenberg et al, 2014; Joyce et al, 2021). Nonetheless, this review yielded some useful guidance for evaluation planners in terms of the fit of methodology with research aims, and the strengths and weaknesses associated with evaluations conducted in an emerging field of study.…”
Section: Discussionmentioning
confidence: 99%